Barriers to and facilitators of asthma care for Malaysian Hajj pilgrims: a qualitative study - Ramli, Rizawati; Khoo, Ee Ming; Liew, Su May; Hanafi, Nik Sherina Haidi; Hussein, Norita; Lee, Ping Yein; Shariff Ghazali, Sazlina; Cheong, Ai Theng; Abu Bakar, Ahmad Ihsan; Abdul Samad, Azah; Abdullah, Suhazeli; Pinnock, Hilary; et al. (Sage Publications, 2023)
Asthma exacerbations are among the commonest reasons for hospitalizations in Malaysian pilgrims during the Hajj. We interviewed 21 stakeholders involved in the pre-Hajj health examination at 14 primary care clinics, to explore their perceptions on barriers to and facilitators of asthma care for Hajj pilgrims. The disadvantages of the short time frame and centralized organization of the pre-Hajj health examinations were viewed as compromising clinicians level of competencies in asthma care, which could potentially be enhanced through more training, audit, and supervision by specialists. Longer time frame to permit sufficient disease control, provision of care by a dedicated asthma team, asthma registry to support continuous care, more resources of long-acting ²-agonist/inhaled corticosteroid, and provision of influenza and pneumococcal vaccines at no cost were the perceived facilitators. Delivery of asthma education, especially the asthma action plan, should be tailored to the level of the pilgrims health literacy and facilitated by educational resources, family engagement, and regular health briefing.